Understanding the relationship between counselor supervisor self-efficacy, the supervisory working alliance, supervisee performance in supervision, and time spent utilizing technology-assisted supervision - Arnold, Täna Marie (Kansas State University, 2022)
As higher education continues to integrate technology as a learning platform so has the counselor education field (Carlisle et al., 2017). This study examined how time spent in technology-assisted supervision influenced counselor supervisor self-efficacy, the supervisory working alliance, and supervisee performance in supervision using Social Cognitive Theory (SCT; Bandura, 1986) as the theoretical framework for the study. Participants in the study were 40 counselor supervisors who were either counselor educators or doctoral students in counselor education and provided weekly supervision to master’s level counselors in training enrolled in either a practicum or internship course. Data were collected by an online survey consisting of a demographic form and three instruments (i.e., Counselor Supervisor Self-Efficacy Scale, Supervisory Working Alliance Inventory, and Counselor Evaluation Rating Scale). Supervisors were encouraged to complete instruments on more than one supervisee; a total of 57 sets of instruments were completed and used for the analysis. The results of the simple linear regression for each of the research questions found no statistical significance of time-spent in technology-assisted supervision predicting counselor supervisor self-efficacy, the supervisory working alliance, or supervisee performance in supervision. The implications of these findings, limitations of this study, and recommendations for future research and practice are described.
Keywords: Technology assisted supervision; Counselor supervisor self-efficacy; Supervisory working alliance; Supervisee performance in supervision